BITUMEN EKSTRAK ASPAL BATU BUTON - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
The needs of bitumen as highway materials has increased, but government has not been capable to fulfill it, so up to now the addition bitumen still be imported. On the other hand, there is Buton rock asphalt deposit, which has not been well exploited, and a tendency in decreasing of the using it in terms of volume. This condition is affected by characteristics of Buton rock asphalt itself and mean while technology for Buton rock asphalt to process it to become pavement materials, which has competitive characteristics to other materials, has not been found yet. Extraction of Buton rock asphalt is a process to obtain a bitumen and to know their characteristic. After that, treatment can be carried out to improve bitumen characteristics, and than exploited as a binder of highway pavement. There are many solvent, which can be adopted in the extraction of Buton rock asphalt. Among many solvents, which have been studied, tri chloroethylene as a solvent has many advantageous. Extract bitumen of tri chloroethylene solvent has characteristics closed to asphalt petroleum specifications and a minarex as an additive will capable to improve its characteristics. Therefore extract bitumen of tri chloroethylene solvent will open an exploitation of Buton rock asphalt as a binder of highway pavement.